The relationship between English and German in Germany: a sociolinguistic study of the use of English and anglicisms, and attitudes towards them - Truslove, K (2020)
This thesis contributes to the study of language and globalisation by exploring the impact of English on German, a ‘supercentral’ language in De Swaan’s terms (2013: 77), at a time when public expressions of concern about English influence on German have become more salient and when some commentators have linked these concerns about language to broader political trends such as the growth of far-right parties in certain parts of the country. Conducted in two phases - the first focusing on the domains considered most at risk of ‘domain loss’, the academic and corporate domains, and the second looking at wider society - this study examines the linguistic impact of English on German (e.g. through the borrowing of vocabulary and the use of English alongside German in Germany) and the social impact this has on Germany by considering how linguistic practices and attitudes vary according to demographic variables, in particular age, level of education, urban/rural and east/west place of residence. It is argued that the alarmist warnings expressed in the media and voiced by politicians and language protectionist groups about English and anglicisms damaging the German language and leading to domain loss are overstated, and that the situation should instead be regarded as one of linguistic gain. Although it was found that young, university-educated German speakers tend to use more English and anglicisms, and be more proficient in English than older, non-university-educated people, and particularly older former East Germans, the majority of informants rejected the idea of German society being divided into English-speaking ‘haves’ and non-English-speaking ‘have-nots’ (Phillipson 2001a). Nonetheless informants acknowledged that people with lower levels of proficiency in English could be marginalised by the increasingly widespread use of English and anglicisms. Given that English is taught as the first foreign language to almost all children across Germany, it is expected that the effect of age and east/west location on linguistic practices and attitudes will subside; the association between educational background and proficiency, usage and attitudes, however, shows no signs of waning, and the issue of exclusion relating to education level and social class is an ongoing concern for the future.